PANCASILA AND RADICALISM: PANCASILA ENCULTURATION STRATEGIES AS RADICAL MOVEMENT PREVENTIONS - S Sudjito; Hendro Muhaimin; Agung Saras Sri Widodo (Jurnal Dinamika Hukum, 2018)
Indonesia has defined Pancasila as nation’s ideology which taught people to live with tolerance. Most Indonesian people embraced Islam and some sects such as salafi, wahabi, jama’ah tabligh, ikhwanul muslimin, and hizbut tahrir which offer alternative for Muslim to know and understand in practising Islamic values individually, group or country (Daulah Isamiyah). The emergence of those various teachings organizations become Islam dynamic. Religion (Islam)-based Radicalism movement is deemed to contradict the state ideology, Pancasila. This article tries to examine organizations or Islamic movement which should be tolerable, respect (lakum dinukum waliyadin), and keep the sovereignty of state. Thus, any Islamic movements that are not based on those principles are convinced that they do not come from Indonesian which is identical with local wisdom and plurality. Keywords: ideology, Pancasila, radicalism, Islam, terrorism